Innovation Strategy to Prevent Child Marriage in Bone Regency (Early Marriage Innovation Case Study) - Andi Adhe Amalya; Risma Niswaty; H, Herman (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
The Innovation Strategy for Preventing Child Marriage or abbreviated as Sip-peka was initiated by the Head of the Bone Regency Regional Development Planning Agency. Sip-sensi was developed as a response to the high number of cases of early marriage in Bone Regency, especially in rural areas because at that time there was no detailed and integrated strategy formulation and it was still running autonomously. The aim of this research is to examine innovation and analyze sustainable strategies for preventing child marriage in Bone Regency. This research is qualitative research with a descriptive type. Data collection techniques used include observation, interviews, documentation and questionnaires. The research results show that the innovation strategy to prevent child marriage in Bone Regency (case study of early marriage innovation) is based on the grand theory of Rogers (2015), including 1) Excellence, lies in the supporting regulations, involving various stakeholders, and using colored bottles as a tool monitoring, 2) Suitability, seen in the involvement of children's forums, life skills education, and religious figures in dialogue and coordination meetings between residents with an interesting approach, 3) Complexity, lies in the process of enforcing sanctions and screening which is carried out strictly by the Religious Courts and P2TP2A in order to obtain dispensation for early marriage, 4) Possibility, seen from the adaptability of innovations that have passed public tests in various villages, districts and provinces, and 5) Convenience, lies in achieving goals 3 and 4 of the SDGs so as to reduce cases of violence, poverty, dropping out of school, maternal, neonatal and infant deaths. The strategy for sustaining innovation in preventing child marriage in Bone Regency is based on SWOT analysis, namely making the village level Puspaga institution an effective center for socializing child marriage regulations and involving children's forums as agents of change in expanding education in the community. This research can be used as a reference in implementing child marriage prevention strategies in various regions because previous studies only focused on mother and baby safety and education rates.